EFFICACY OF INTR A ARTICULAR INJECTIONS OF GENTAMYCIN IN GOUT ARTHRITIS - R N Protopopova; S Erdesz; V G Krivoshapkin (Научно-практическая ревматология)
Summary» Aim: To study the incidence ofjoints complaints aimed at determining group for further clinical examination. Material and methods: Simultaneous continuous epidemiological study among residents of four typical rural settlements in the Republic of Saha (Yakutia) with scanning questionaire was used. Results: At the result of questionaire of570 persons with joint pains and 735 with spinal pains were found which amounted to 46.9% and 60.4% of examined population correspondingly. Conclusion: Joint and spinal complains are frequent manifestations with increasing distribation in older aged groups.